Isolation and Genomic Characterization of ‘Desulfuromonas soudanensis WTL’, a Metal- and Electrode-Respiring Bacterium from Anoxic Deep Subsurface Brine - Badalamenti, Jonathan P.; Summers, Zarath M.; Chan, Chi Ho; Gralnick, Jeffrey A.; Bond, Daniel R. (Frontiers in Microbiology, 2016)
Reaching a depth of 713 m below the surface, the Soudan Underground Iron Mine (Soudan, Minnesota, USA) transects a massive Archaean (2.7 Ga) banded iron formation, providing a remarkably accessible window into the terrestrial deep biosphere. Despite organic carbon limitation, metal-reducing microbial communities are present in potentially ancient anoxic brines continuously emanating from exploratory boreholes on Level 27. Using graphite electrodes deposited in situ as bait, we electrochemically enriched and isolated a novel halophilic iron-reducing Deltaproteobacterium, ‘Desulfuromonas soudanensis’ strain WTL, from an acetate-fed three-electrode bioreactor poised at +0.24 V (vs. standard hydrogen electrode). Cyclic voltammetry revealed that ‘D. soudanensis’ releases electrons at redox potentials approximately 100 mV more positive than the model freshwater surface isolate Geobacter sulfurreducens, suggesting that its extracellular respiration is tuned for higher potential electron acceptors. ‘D. soudanensis’ contains a 3,958,620-bp circular genome, assembled to completion using single-molecule real-time (SMRT) sequencing reads, which encodes a complete TCA cycle, 38 putative multiheme c-type cytochromes, one of which contains 69 heme-binding motifs, and a LuxI/LuxR quorum sensing cassette that produces an unidentified N-acyl homoserine lactone. Another cytochrome is predicted to lie within a putative prophage, suggesting that horizontal gene transfer plays a role in respiratory flexibility among metal reducers. Isolation of ‘D. soudanensis’ underscores the utility of electrode-based approaches for enriching rare metal reducers from a wide range of habitats.